Pengembangan Booklet Tumbuhan Paku di Taman Hutan Raya Sultan Thaha Syaifuddin Sebagai Bahan Pengayaan Mata Kuliah Taksonomi Tumbuhan : The Development of Booklet on the Subject Matter of Ferns (Pteridophytes) from the Sultan Thaha Syaifuddin's Forest Park as Enrichment Material of Plant Taxonomy Course - Muswita Muswita; Upik Yelianti; Lia Kusuma; Amita Intan (BIODIK, 2020)
T The research aims to develop and determine the feasibility of Ferns booklets in Tahura STS. This type of research is Research and Development research using ADDIE learning design models. The booklet that was developed contains 42 types of Ferns that grow in Tahura STS, consisting of 14 types of epipitic Ferns and 28 types of terrestrial Ferns. The booklet that was developed contains scientific names, pictures, classifications and descriptions of ferns that grow in Tahura STS. Validation of media experts was carried out twice with a final score of 85.71% with the category "Very Good". Content expert validation was carried out twice with a final score of 92.8% in the "Very Good" category. Thus the product developed is worth testing. The percentage of small group trials on booklets was 89.6% in the "very good" category. The percentage of large group trials on booklet results was 90.9% in the "very good" category. The lecturer's response to the booklet of Ferns in Tahura STS was 83.9% in the "very good" category. Based on the validation of the experts and the results of small and large group trials and lecturer responses it can be concluded that the booklet of Ferns in Tahura STS is suitable to use as an enrichment for Plant Taxonomy courses. Keywords: booklet, enrichment material, Ferns. Abstrak. Penelitian bertujuan untuk mengembangkan dan mengetahui kelayakan booklet tumbuhan paku di tahura STS. Jenis penelitian adalah penelitian Research and Development dengan menggunakan model desain pembelajaran ADDIE. Booklet yang dikembangkan memuat 42 jenis paku yang tumbuh di Tahura STS, terdiri dari 14 jenis paku epipit dan 28 jenis paku teresterial. Booklet yang dikembangkan memuat nama ilmiah, gambar, klasifikasi dan deskripsi dari tumbuhan paku yang tumbuh di Tahura STS. Validasi ahli media dilakukan sebanyak dua kali dengan nilai akhir 85,71% dengan kategori â€œSangat Baikâ€. Validasi ahli materi dilakukan sebanyak dua kali dengan nilai akhir 92.8% dengan kategori â€œSangat Baikâ€. Dengan demikian produk yang dikembangkan layak untuk diujicobakan. Persentase ujicoba kelompok kecil terhadap booklet sebesar 89,6% dengan kategori â€œsangat baikâ€. Persentase ujicoba kelompok besar terhadap booklet hasil sebesar 90,9% dengan kategori â€œsangat baikâ€. Respon dosen terhadap booklet tumbuhan paku di Tahura STS sebesar 83,9% dengan kategori â€œsangat baikâ€. Berdasarkan validasi ahli media dan hasil ujicoba kelompok kecil dan besar serta respon dosen dapat disimpulkan booklet tumbuhan paku di Tahura STS layak digunakan sebagai vahan pengayaan mata kuliah taksonomi tumbuhan. Kata kunci: booklet, bahan pengayaan, tumbuhan paku.